Stress &Amp; Well-Being at Work: Assessments and Interventions for Occupational Mental Health.
DOI: 10.1037/10116-016
|View full text |Cite
|
Sign up to set email alerts
|

Job stress and employee counterproductivity.

Abstract: Job Stress and Employee CounterproductivityOccupational stress can be thought of as job-related discomfort or illness that people experience because of their work situations (Beehr, 1991). This discomfort may manifest itself in a variety of ways, including coronary heart disease, headaches, restless sleep, fatigue, other somatic symptoms, and decreases in individual performance on the job (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…Increased cigarette smoking (e.g. Conway et al, 1981;Parrott, 1995) and consumption of drugs or alcohol ( Jones and Boye, 1992) are common examples of behavioural strain. Job stress tends to be associated with higher levels of alcohol consumption and alcohol related problems particularly for individuals who endorse escapist reasons for drinking (Grundberg et al, 1999).…”
Section: What We Know So Farmentioning
confidence: 99%
“…Increased cigarette smoking (e.g. Conway et al, 1981;Parrott, 1995) and consumption of drugs or alcohol ( Jones and Boye, 1992) are common examples of behavioural strain. Job stress tends to be associated with higher levels of alcohol consumption and alcohol related problems particularly for individuals who endorse escapist reasons for drinking (Grundberg et al, 1999).…”
Section: What We Know So Farmentioning
confidence: 99%
“…Another study of nurses by Motowildo, Packard, and Manning (1986) showed that both the frequency and intensity of stressful job events were related to work behaviors. Additionally, some researchers have operationalized behavioral responses as employee theft, sabotage, or aggression, finding a consistently positive relationship between levels of job stress and these three measures (Chen & Spector, 1991;Jones & Boye, 1992). In sum, it seems that elevated levels of occupational stress typically result in negative psychological, physical, and behavioral outcomes.…”
Section: Potential Strainsmentioning
confidence: 99%
“…Many skilled and talented nurses become disillusioned and leave nursing or take additional training so that they can work in educational or administrative positions, thus depriving the clinical areas of experienced personnel (Pines & Kafry 1981). Edelwich & Brodsky (1980) and Jones (1981) described staff burnout in detail, including individual, social and situational factors associated with it.…”
Section: Burnout Aetiologymentioning
confidence: 99%
“…A universally accepted definition of burnout is required. Jones (1981) suggests that one way to achieve this goal is to develop a valid and rehable psychological test to measure burnout. 2 Help detect the early signs of burnout and evaluate the effectiveness of current intervention strategies, e.g.…”
Section: Further Researchmentioning
confidence: 99%